Connections among farsighted agents - Vincent Vannetelbosch; Gilles Grandjean; Ana Mauleon (Fondazione Eni Enrico Mattei (FEEM), 2009)
We study the stability of social and economic networks when players are farsighted. In particular, we examine whether the networks formed by farsighted players are different from those formed by myopic players. We adopt Herings, Mauleon and Vannetelbosch's (Games and Economic Behavior, forthcoming) notion of pairwise farsightedly stable set. We first investigate in some classical models of social and economic networks whether the pairwise farsightedly stable sets of networks coincide with the set of pairwise (myopically) stable networks and the set of strongly efficient networks. We then provide some primitive conditions on value functions and allocation rules so that the set of strongly efficient networks is the unique pairwise farsightedly stable set. Under the componentwise egalitarian allocation rule, the set of strongly efficient networks and the set of pairwise (myopically) stable networks that are immune to coalitional deviations are the unique pairwise farsightedly stable set if and only if the value function is top convex.
Keywords: A14; C70; D20; 330; Farsighted Players; Stability; Efficiency; Connections Model; Buyerseller Networks